Pick the Freshmen Up for a “Healthy Study Start” Evaluation of a Health Promoting Onboarding Program for First Year Students at the Carinthia University of Applied Sciences, Austria - Limarutti, Andrea; Maier, Marco Johannes; Mir, Eva; Gebhard, Doris (Frontiers in Public Health, 2021)
Introduction: Universities are an essential setting for creating health promoting environments. Evidence shows that university life can pose various threats to the students' health. Especially first year students are vulnerable to mental health issues. To support well-being and prevent psychological distress from the first day of studying, onboarding programs are needed to promote the students' health and their self- and social competencies. The study demonstrates a tailored multi-component onboarding intervention program named “Healthy Study Start.” An evaluation of the effectiveness is presented focusing on outcomes regarding the students' sense of coherence (S-SoC), social support, sympathy, the work-related collective and the participative safety (a sub-scale of the team climate) among freshmen at the Carinthia University of Applied Sciences (CUAS, Austria). Methods: For the analyses, a quantitative controlled study design was used and results were measured three times. The intervention group (n = 72) was composed of freshmen selected from the bachelor study programs Occupational Therapy, Speech and Language Therapy, Biomedical Science and Radiologic Technology. Freshmen from the bachelor study program Healthcare and Nursing formed the control group (n = 81). As the requirements for analyses of variance were not fulfilled, the data had to be analyzed using e.g., Mann-Whitney U-tests. Results: Significant changes (all p < 0.016) between the two groups were found between T0/T1, and between T0/T2. Furthermore, changes within the intervention group (all p < 0.016) emerged in nearly all outcomes between T0/T1, while within the control group no changes were identified. However, the intervention group had statistically significantly higher values in the majority of outcomes at T1 and T2 compared to the control group. Conclusion: The onboarding program “Healthy Study Start” shows how an initiative at the beginning of their studies can support students in entering a new phase of their lives. The results indicate a positive effect on the students' self- and social competencies. However, students' health promotion is not only an investment for a health conscious university or an enhanced employability. Especially in health-related fields of study, students are future multipliers and play an essential role in implementing health promotion concepts for clients, patients and employees.